Puns: The Functions and Translation Strategies in The Hidden Oracle Novel by Rick Riordan - Amadeus, Josephine Sebastiana; Kurniati, Nur Utami Sari’at; Widodo, Jordy Satria (ITScience (Information Technology and Science), 2025)
Pun is a type of figure of speech that manipulates sound or meaning. In narrative discourse, pun serves not only as humor but also establishes thematic coherence as well as poetic and dramatic effects. Consequently, the use of puns poses a challenge in translation, as it involves different linguistic features and cultural references. This study examined the functions and translation strategies of puns in The Hidden Oracle novel by Rick Riordan. An author, particularly in children’s and young adult (YA), renowned for integrating puns and intertextuality with Greek and Roman mythology in his works. This research employed Delabastita’s (1993, 1996) theories to examine the strategies of pun translation. Additionally, a synthesis of Delabastita’s (1993) and Harding’s (2017) theories was applied to analyze the functions of puns. Using the descriptive qualitative method, this article compares the source text and the target text to explore how the pun is preserved, shifted, or lost, as well as its impact on its function. Of the 31 data, 17 of them serve to add thematic coherence and humor simultaneously. In its translation, however, over half of the puns are not preserved but rendered through non-puns, related rhetorical devices, and many more. These findings show that the translation of The Hidden Oracle novel tends to prioritize rendering the main message over style. Thus, establishing that the interconnected aspects of the functions of puns in their translation influence the translated novel’s overall coherence and narrative effects, such as humor, tension and attention, and taboo.